Production of colchicine induced tetraploids in Vicia villosa roth - (:unkn) unknown (FIRENZE UNIV PRESS, 2010)
Seeds V villosa (hairy vetch) were treated with 0.005% colchicine and 12% tetraploid plants (2n=4x=28) were obtained. Besides two chimeric plants, one of them consisted of diploid, triploid, tetraploid, hexaploid, heptaploid, octoploid roots and the other diploid and triploid roots were also obtained in hairy vetch. Tetraploid plants were determined by the chromosome numbers in the root tips which were confirmed by studies conducted in the pollen mother cells (PMCs). Chromosome irregularities in the PMCs of diploids were not observed, however normal and abnormal chromosomal behavior were detected in tetraploids. The morphological observations pointed out those tetraploids were shorter, surface of leaves were greater, and size of stomata were bigger but the number of stomata in per area were less than diploids. Flowering was delayed in tetraploids, the number of flowers was less, but forming a few larger flowers than diploids. It was also observed that the colour of leaves was darker, and amount of total chlorophyll in the leaves was higher in tetraploids. Pollen grains also showed some differences in diploids and tetraploids. While diploid pollen grains had tricolporate, numbers of pore and colpi showed variations in tetraploids; pollen grains with 4 pores and 4 colpi, 5 pores and 5 colpi and 6 pores and 6 colpi were identified. The pollen size in the tetraploids was defined bigger than others. There were differences in the shapes of pollen grains; they were elliptical in diploids, triangular in polyploids. Pollen viability was measured as 99% in diploids, and this rate lowered to 81% in tetraploids.
Keywords: chimeric plants; colchicine; hairy vetch; pollen; polyploidy; stomata; Vicia villosa; PLOIDY LEVEL; LENGTH; WATERMELON; INDICATOR; ORIGIN; PLANTS; DNA